Transformasi Adobe Flash dalam Dunia Pendidikan: Analisis Bibliometrik (2006-2023) - Zafrullah, Zafrullah; Annisa Fitriani; Atika Miftah Ramadhani; Siti Muflihah Nur Hidayah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The use of Adobe Flash in multimedia-based learning media in the world of education is expected to improve the quality and availability of learning resources in various fields, including creating more innovative and efficient learning experiences. As a result, many studies have highlighted the use of Adobe Flash as a research focus. This bibliometric research aims to evaluate previous academic work that has been carried out in the context of the use of Adobe Flash in education. Research Method using bibliometric analysis from the Scopus Database. From the results of the analysis, it appears that there are 185 sources that review Adobe Flash in education, including articles, proceedings, and reviews. Despite fluctuations, from 2010 to 2012, there was an increase in the number of publications which then decreased from 2013 to 2017, before rising again in 2018 and peaking in 2020. The three main research groups examining the role of Adobe Flash in education come from Indonesia, with a total of 35 articles. Two top authors from Indonesia and two from Malaysia, as well as one from Turkey, topped the rankings in number of publications. O'Byrne is the researcher with the highest citations, while Wang, Susilowati, Anaraki, and Gregorius are in the top five with significant citations. In future research, considering learning process, mathematics learning, learning media, interactive multimedia, development models, and research models as a focus could be an interesting choice